2016
DOI: 10.3329/bjmm.v1i2.21509
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis E Virus (HEV) Infection Among Patients Attending BSMMU, Dhaka

Abstract: The present study was done to determine the seroprevalence of the infection by Hepatitis E virus (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Among pregnant women living in rural areas, the HEV infection rate is 46 cases/per 1000 person-year [ 56 ]. A prevalence survey among patients admitted to hospitals with hepatitis showed HEV caused 35% of sporadic acute hepatitis [ 57 ] and 22% of acute-on-chronic liver disease in Dhaka in 2008 [ 58 ]. An earlier survey from 2004 to 2006 identified HEV as the cause for 58% of general patients, 45% of pregnant patients with acute hepatitis, and 56% of cases with hepatic failure in Dhaka [ 19 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Among pregnant women living in rural areas, the HEV infection rate is 46 cases/per 1000 person-year [ 56 ]. A prevalence survey among patients admitted to hospitals with hepatitis showed HEV caused 35% of sporadic acute hepatitis [ 57 ] and 22% of acute-on-chronic liver disease in Dhaka in 2008 [ 58 ]. An earlier survey from 2004 to 2006 identified HEV as the cause for 58% of general patients, 45% of pregnant patients with acute hepatitis, and 56% of cases with hepatic failure in Dhaka [ 19 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…19 A small proportion of subjects of many industrialized countries found to have circulatory antibodies to HEV, while in Bangladesh which is endemic for HEV and where seroprevalence rate of anti-HEV IgG antibodies are higher though considerable variations have been observed in other studies in Bangladesh. 20,7 In our study, seroprevalence of anti-HEV IgG on pregnant women demonstrates the high prevalence (37.6%), a considerable potential for the transmission of HEV infection in pregnant women. In one study from rural area Matlab, Chandpur reported lower anti-HEV positivity rates (22.5%, 255 out of 1134) in asymptomatic healthy subjects and another study from BSMMU, Dhaka also reported nearly same prevalence (20.6%) of anti-HEV IgG in people of The overall seroprevalence of HEV infection among pregnant women in Bangladesh is higher than the results of other studies done in Ghana (28.66%) 23 , India (33.67%) 19 , United Arab Emirates (20%) 24 , Gabon (14.1%) 25 , but lower than that in Egypt (84.3%) 26 , Ethiopia (59%) 27 , and Sudan (41.1%) 28 .…”
Section: Discussionmentioning
confidence: 99%
“…It causes epidemics, especially in developing countries where sanitation and hygienic practices are poor and drinking water supplies are often contaminated by sewage. 20 Pregnant women are at increased risk of contracting acute HEV infection that often leads to acute liver failure. 21 A study done at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka on 31 pregnant women indicated HEV as a principal etiological agent (45.16%) for acute hepatitis, the fatality for which approaches >75% when the infection occurs in the second/ third trimester of pregnancy with fulminant hepatic failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bangladesh has a high HEV burden, where small outbreaks are common. The prevalence of HEV antibody among the general population is 22%-60% [20][21][22]; the incidence of HEV seroconversion is 40 per 1,000 people per year in rural settings [21]. Drinking municipal tap water, outdoor employment, recent urban travel, and recent contact with a patient with jaundice have been identified as HEV infection risk factors [21,23].…”
Section: Plos Onementioning
confidence: 99%